XRmas: Extended Reality Multi-Agency Spaces for a Magical Remote Christmas - Zhang, Yaying; Jones, Brennan; Rintel, Sean; Neustaedter, Carman (2021)
The COVID-19 pandemic has raised attention toward remote and hybrid communications. Currently, one highly-studied solution lets a remote user use virtual reality (VR) to enter an immersive view of a local space, and local users use augmented reality (AR) to see the remote user’s representation and digital contents. Such systems give the remote user a sense of ‘being there’, but we identify two more challenges to address. First, current systems provide remote users with limited agency to control objects and influence the local space. It is necessary to further explore the relationship between users, virtual objects, and physical objects, and how they can play a role in providing richer agency. Second, current systems often try to replicate in-person experiences, but hardly surpass them. We propose XRmas: an AR/VR telepresence system that (1) provides a multi-agency space that allows a remote user to manipulate both virtual and physical objects in a local space, and (2) introduces three family activities in a Christmas context that adopt holographic animation effects to create a ‘magical’ experience that takes users beyond merely the feeling of ‘being there’. We report on preliminary insights from the use of such a system in a remote family communication context.